Monetary Regimes, Inflation And Monetary Reform: An Essay in Honor of Axel Leijonhufvud - Michael D. Bordo; Lars Jonung (Rutgers University, Department of Economics, 1994)
Over the past decade and a half Axel Leijonhufvud has written extensively on monetary regimes and their connection to nominal and real economic performance. Monetary regimes are important because they determine whether countries follow stable or unstable monetary policies and hence have stable or inflationary price levels. Each monetary regime is associated with a given set of inflationary expectations of the private sector and a pattern of reactions to these expectations by the monetary authorities. The state of the private sector's expectations, specific to each regime, in turn greatly influences the response of real variables to monetary policy actions.
Keywords: E5; 330; axel leijonhufvud; inflation; monetary regimes